2020
DOI: 10.1002/celc.202001319
|View full text |Cite
|
Sign up to set email alerts
|

Promoting the Electrocatalytic Activity of Ti3C2Tx MXene by Modulating CO2 Adsorption through Oxygen Vacancies for High‐Performance Lithium‐Carbon Dioxide Batteries

Abstract: Lithium‐carbon dioxide (Li‐CO2) batteries are considered as a most auspicious energy storage systems owing to their high capacity and the ability of capturing CO2. However, there are still some critical issues needed to be addressed before their practical application, such as high charge potential and poor cyclability. Herein, oxygen vacancy‐enriched TiO2 nanoparticles grown in situ on Ti3C2Tx MXene (OV‐TiO2/MXene) are synthesized as catalysts for Li‐CO2 batteries by facile one‐step ethanol heat treatment of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 64 publications
0
7
0
Order By: Relevance
“…Both the gravimetric current density and the capacity were improved significantly with an achieved current density of 5–50 times and a capacity of 5–100 times compared to other works. [ 20,25,27,28,40–62 ] The areal current density and the capacity were also enhanced compared to literature, [ 23,26,63,64 ] as shown in Figure S15 (Supporting Information).…”
Section: Resultsmentioning
confidence: 64%
“…Both the gravimetric current density and the capacity were improved significantly with an achieved current density of 5–50 times and a capacity of 5–100 times compared to other works. [ 20,25,27,28,40–62 ] The areal current density and the capacity were also enhanced compared to literature, [ 23,26,63,64 ] as shown in Figure S15 (Supporting Information).…”
Section: Resultsmentioning
confidence: 64%
“…12d). 142 The SEM image (Fig. 12e) revealed that the Ov-TiO 2 nanoparticles were uniformly distributed on the potato chip-like MXene with a large amount of space, which facilitated the sufficient contact among CO 2 , the electrolyte and the material, and thus accelerated the CO 2 RR and CO 2 ER kinetics.…”
Section: Mxene Catalystsmentioning
confidence: 99%
“…134 A lot of research about MXene-based cathodes has been done. [150][151][152] Zhang et al 153 prepared a two-dimensional MXene (Fe/Co-Fig. 11 Schematic diagram of the preparation and structure of "woody carbon nanolayers".…”
Section: Electrospinningmentioning
confidence: 99%
“…134 A lot of research about MXene-based cathodes has been done. 150–152 Zhang et al 153 prepared a two-dimensional MXene (Fe/Co-CNT@MXene-T) anchored CoFe nano-alloy modified carbon nanotube (CNT) 3D structure dual-function catalyst. Using the active site of CoFe nanoparticles, the strong sheath and fast charge transfer provided by carbon nanotubes and MXene, the Zn–air battery with this air electrode shows a capacity density of 759 mA h g −1 at 10 mA cm −2 , and a power density of 138 mW cm −2 at 250 mA cm −2 .…”
Section: Challenges For Air Electrodes and Solutionsmentioning
confidence: 99%